Kindergarten Students' and Parents' Perceptions of Science Classroom Environments: Achievement and Attitudes - Robinson, Esther; Fraser, Barry (Springer, 2013)
This study, involving the modification, validation and use of a learning environment questionnaire for both kindergarten students and their parents, is significant because prior learning environment research has normally involved neither parents nor such young students. A questionnaire, which was based on the What Is Happening In this Class? and assessed actual and preferred teacher support, involvement, cooperation and equity, exhibited sound factorial validity, internal consistency reliability and the ability to differentiate between classrooms. Parents perceived a more favourable actual classroom environment than students, but students preferred a more favourable environment than parents. Associations were found between kindergarten students’ achievement and attitudes and the nature of the learning environment.